PENGEMBANGAN UMKM BERBASIS INOVASI PRODUK DAN E-COMMERCE DI DESA WANGON BANYUMAS - Endra Saputra; Nur Isna Inayati; Annisa Ilma Hartikasari (Jurnal Abdimas Sangkabira, 2021)
The management of new products is a form of innovation that boosts the economy of the local area and even the state. Empowerment of the social community through the MSME development approach through community groups will have a positive impact on village development, especially in Wangon Village, Banyumas Regency. The thing that underlies this service is the existence of a superior commodity in the village of Wangon, namely in the form of brown sugar which can be used as a new product that can increase local income. The problems faced by the community are the absence of modern technology that accelerates the production process as well as bookkeeping and marketing that can add to the production process and smooth production.